High-Energy and High-Power Pseudocapacitor–Battery Hybrid Sodium-Ion Capacitor with Na+ Intercalation Pseudocapacitance Anode - Wei, Qiulong; Li, Qidong; Jiang, Yalong; Zhao, Yunlong; Tan, Shuangshuang; Dong, Jun; Mai, Liqiang; Peng, Dong‑Liang (Nano-Micro Letters, 2021)
High-performance and low-cost sodium-ion capacitors (SICs) show tremendous potential applications in public transport and grid energy storage. However, conventional SICs are limited by the low specific capacity, poor rate capability, and low initial coulombic efficiency (ICE) of anode materials. Herein, we report layered iron vanadate (Fe5V15O39 (OH)9·9H2O) ultrathin nanosheets with a thickness of 2.2 nm (FeVO UNSs) as a novel anode for rapid and reversible sodium-ion storage. According to in situ synchrotron X-ray diffractions and electrochemical analysis, the storage mechanism of FeVO UNSs anode is Na+ intercalation pseudocapacitance under a safe potential window. The FeVO UNSs anode delivers high ICE (93.86%), high reversible capacity (292 mAh g−1), excellent cycling stability, and remarkable rate capability. Furthermore, a pseudocapacitor–battery hybrid SIC (PBH-SIC) consisting of pseudocapacitor-type FeVO UNSs anode and battery-type Na3(VO)2(PO4)2F cathode is assembled with the elimination of presodiation treatments. The PBH-SIC involves faradaic reaction on both cathode and anode materials, delivering a high energy density of 126 Wh kg−1 at 91 W kg−1, a high power density of 7.6 kW kg−1 with an energy density of 43 Wh kg−1, and 9000 stable cycles. The tunable vanadate materials with high-performance Na+ intercalation pseudocapacitance provide a direction for developing next-generation high-energy capacitors. Highlights: 1 Layered iron vanadate ultrathin nanosheets (FeVO UNSs) with a thickness of 2.2 nm were synthesized by a sonicate-assisted method. 2 Pseudocapacitive Na+ intercalation of FeVO UNSs anode delivers high initial coulombic efficiency (93.86%), high reversible capacity (292 mAh g−1), excellent rate capability, and remarkable cycling stability. 3 A pseudocapacitor–battery hybrid SIC is assembled with the elimination of presodiation and delivers high energy and power densities.